Homo mundanus: Zur Verschränkung von conditio humana und conditio mundana bei Hannah Arendt - Höfer, Evelyn Wiebke (HannahArendt.net, 2022)
With Arendt, to ask about people is to ask about the world. To ask about the world is to ask about people. The specifically human activities of acting and producing as well as the specifically human freedom are conditions of world, while worldliness and plurality, which are referred to the world, are conditions of the world-forming activities. This mutual referentiality of human beings and world in Arendt leads to the thesis that human beings are to be understood as world beings of a human world through the entanglement of conditio humana and conditio mundana, which was first introduced as a concept by Christina Schües. The human world being as a potential is represented in the concept of homo mundanus or homines mundani. Through the interweaving of conditio humana and conditio mundana, it can be shown that the loss of the world, which Arendt describes in “The Human Condition” as the development of modern times, can be cancelled out in the (re)gain of the world. According to Arendt, the world as a space of reference is closely connected to the political. Therefore, the question is whether the thesis of human beings as world beings can be extended to a dimension of world citizenship. This extension of world to cosmopolis must, however, be rejected with Arendt, because the world as space requires delimitations, which cosmopolitanism seeks to delimit.